MODELLING OF A STOCHASTIC CONTINUOUS SYSTEM - Albertyn, Martin; Kruger, Paul S. (The South African Journal of Industrial Engineering, 2012)
The key objective is to develop a method which can be utilized to model a stochastic continuous system. A system from the "real world" is used as the basis for the simulation modelling technique that is presented. The conceptualization phase indicates that the model has to incorporate stochastic and deterministic elements. A method is developed that utilizes the discrete simulation ability of a stochastic package (ARENA), in conjunction with a deterministic package (FORTRAN), to model the continuous system. (Software packages tend to specialize in either stochastic, or deterministic modelling.) The length of the iteration time interval and adequate sample size are investigated. The method is authenticated by the verification and validation ofthe defined model. Two scenarios are modelled and the results are discussed . Conclusions are presented and strengths and weaknesses of this method are considered and discussed .